Penggunaan secondary skin pada fasad bangunan di Indonesia - Chairina, Fitra (Maliki Interdisciplinary Journal, 2024)
The use of secondary skin on building facades in Indonesia is increasingly popular as an innovative solution to overcome tropical climate challenges. Secondary skin functions to block sunlight, reduce heat, and increase energy efficiency. Materials used include wood, metal, and bamboo, each with advantages and disadvantages. Wood offers a natural look and is effective as an insulator, but requires professional maintenance. Metal is strong and durable, but it can absorb heat and requires a strong support structure. Bamboo is suitable for traditional designs but is less durable against exposure to sunlight. Flexible designs such as grilles that can be opened and closed are very suitable for Indonesia’s two-season climate. The integration of a vertical garden as a secondary skin also beautifies the facade and improves air quality. Despite increasing construction costs, secondary skin offers aesthetic, comfort, and energy efficiency benefits, making it an option worth considering. This article explores the various aspects and benefits of using secondary skin in Indonesia as well as material and design considerations appropriate to the tropical climate.